Vickerey allocation rule with income effect - Hiroki Saitoh; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2005)
We consider situations where a society tries to efficiently allocate several homogeneous and indivisible goods among agents. Each agent receives at most one unit of the good. For example, suppose that a government wishes to allocate a fixed number of licenses to operate in its country to private companies with highest abilities to utilize the licenses. Usually companies with higher abilities can make more profits by licenses and are willing to pay higher prices for them. Thus, auction mechanisms are often employed to extract the information on companies' abilities and to allocate licenses efficiently. However, if prices are too high, they may damage companies' abilities to operate. Generally high prices may change the benefits agents obtain from the goods unless agents' preferences are quasi-linear, and we call it 'income effect'. In this paper, we establish that on domains including nonquasi-linear preferences, that is, preferences exhibiting income effect, an allocation rule which satisfies Pareto-efficiency, strategy-proofness, individual rationality, and nonnegative payment uniquely exists and it is the Vickrey allocation rule.
Keywords: D44; C78; D71; D61; D82; 330; Vickrey auction; allocation rule; income effect; strategy-proofness; Auktionstheorie; Allokation; Einkommenseffekt; Verhandlungstheorie; Neue politische Ökonomie; Strategie